1995
DOI: 10.1139/f95-862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gut content in immature aquatic insects on assessments of environmental metal contamination

Abstract: We evaluated the effect of metal associated with the gut content in immature aquatic insects (larvae and nymphs) on spatial and interspecific comparisons of whole-body metal concentrations. Four species, common to cobble-bottom rivers and streams, were collected along an established contamination gradient in the Clark Fork River, and from tributaries of the Clark Fork. Metal concentrations were determined in the gut and its content and in the insect body. Whole-body metal concentrations were higher and more va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…These estimated gut contents are within the range of those commonly observed for L. variegatus [6,[14][15][16][17], reinforcing the presumption that purging of sediment from the gut is the primary cause of the initial rapid decline in body burden rather than loss from some other internal metal pool. Variability of total metal body burdens generally decreased after gut contents were eliminated, as previously noted by Cain [18].…”
Section: Resultssupporting
confidence: 73%
“…These estimated gut contents are within the range of those commonly observed for L. variegatus [6,[14][15][16][17], reinforcing the presumption that purging of sediment from the gut is the primary cause of the initial rapid decline in body burden rather than loss from some other internal metal pool. Variability of total metal body burdens generally decreased after gut contents were eliminated, as previously noted by Cain [18].…”
Section: Resultssupporting
confidence: 73%
“…In studies of uptake of xenobiotics, this has been reported to result in considerable overestimation of body burdens (e.g. Cain et al 1995) or estimates of uptake rate (e.g. Odin et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Starvation may be useful to eliminate chemical contaminants, but this has not been demonstrated so far. It is known, for aquatic insects, that the gut content can contribute significantly to the total body load of chemical pollutants (Cain, Luoma, & Axtmann, 1995). Furthermore, faeces of mealworm larvae that were fed with a deoxynivalenol (DON)-contaminated substrate were found to contain the mycotoxin (van Broekhoven, 2014in EFSA scientific committee, 2015.…”
Section: Accepted Manuscriptmentioning
confidence: 99%